The clinical potential of meniscal progenitor cells - Wan-Ting Yan; Jing-Song Wang; Peng-Zhou Fan; Sally Roberts; Karina Wright; Zheng-Zheng Zhang (Journal of Cartilage & Joint Preservation)
Introduction: The meniscus is an important cushioning structure of the knee joint, with the maintenance of its normal structure and function playing a crucial role in protecting the joint from early degeneration. Stem/progenitor cells could be the key to help researchers to have a deeper understanding of the biological process of meniscal injury repair and may be important in the meniscus tissue regeneration processes. To the best of our knowledge, there is currently a lack of comprehensive reviews on existing research about the meniscus progenitor cells (MPCs). Objectives: By reviewing the existing MPC literature, we aim to provide insights for future research on meniscus regeneration. Methods: The isolation methods, biological characteristics and the translational application of MPCs were summarized. Results: MPCs could be isolated according to their colony-forming ability, marker expression, migration ability, and differential adhesion to fibronectin. Most existing studies on surface markers of MPCs have largely followed the paradigm of mesenchymal stromal/stem cell research. Based on the information provided by their surface markers and expression profile, researchers located MPCs in the peripheral surface area of the meniscus. Few researches have investigated the translation and application of MPCs, with most studies being limited to MPCs extraction and subsequent reimplantation in vivo. Conclusions: MPCs are a group of meniscus-resident cells, which exhibit certain stem/progenitor cell characteristics, such as the ability to undergo multilineage differentiation in in vitro culture.